1991
DOI: 10.1515/bmte.1991.36.5.120
|View full text |Cite
|
Sign up to set email alerts
|

Die Knochenzemententfernung mit dem Laser - Bone Cement Removal with the Laser

Abstract: In operations requiring replacement of cemented endoprothesis, the removal of both the prosthesis and the cement is often difficult as the cement adheres strongly to the bone. Mechanical removal frequently results in fenestration or traumatisation of the bone. The aim of non-contact removal of polymethylmethacrylate (PMMA) with the laser, is to access normally inaccessible regions while inflicting a minimum amount of damage to the bone substance. The much cited cw or superpulsed CO2-laser cannot be used clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This paper therefore proves that it could indeed be suggested 12 to reduce or completely abolish the utilization of colorant dopants in the preparation of the bone cement mixture, since the mathematical calculation proves that ␣ > 500 cm Ϫ1 . This decision would reduce or avoid the deterioration of mechanical characteristics of bone cement itself, which can cause bone deterioration during the bone cement removal procedure.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…This paper therefore proves that it could indeed be suggested 12 to reduce or completely abolish the utilization of colorant dopants in the preparation of the bone cement mixture, since the mathematical calculation proves that ␣ > 500 cm Ϫ1 . This decision would reduce or avoid the deterioration of mechanical characteristics of bone cement itself, which can cause bone deterioration during the bone cement removal procedure.…”
Section: Resultsmentioning
confidence: 53%
“…For example, Scholz et al 12 consider the fact that colorant dopants of bone cement strongly bind to PMMA, and if the absorption coefficient of the PMMA would be larger than 500 cm Ϫ1 , the dopants themselves could be reduced or abolished completely in the preparation of the mixture of bone cement. This would reduce trauma to the bone caused by a high percentage of colorants, which occurs during the removal procedure of the cement using laser techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Braren et al [27] demonstrated the use of excimer laser for the material removal of bone cement, but in experiments this tool was very slow. Scholz et al [28] found that carbon dioxide laser showed the best effect, but is currently used rarely. Caillouette et al [29], deSteiger et al [31] and Smith et al [32] described a new ultrasonically-driven tool for the removal of bone cement.…”
Section: Introductionmentioning
confidence: 99%